Effects of HRV biofeedback training on reducing anxiety-, stress- and traumatic stress symptoms among police officers in Iceland - Katrín Ása Karlsdóttir 1995- (2023)
In their occupation, police officers experience stressful situations, witness traumatic events, and have to make critical decisions under high pressure. These circumstances can take a toll on the officer‘s mental health. Research has shown that HRV biofeedback training can significantly improve individuals' mental health. Therefore, the present study aimed to examine the effects of HRV biofeedback training in reducing Icelandic police officers' anxiety-, stress-, and traumatic stress symptoms. The research was conducted over ten weeks. Participants were randomly assigned to one of two groups: an intervention group that received the HRV biofeedback training at the beginning and a wait-list control group that received the training at week five. All participants took part in a questionnaire that included the DASS-Anxiety, PCL-5, PSQ-Op, and PSQ-Org, baseline measurements, and individual training where customized breathing frequency was found for each participant, which maximized their heart rate variability. The results did not show a significant main- or interaction effect between the HRV biofeedback training and anxiety-, stress-, and traumatic stress symptoms. However, there was a noticeable decrease in stress for the intervention group measured by PSQ-Op and PSQ-Org, questionnaires specifically designed to measure factors related to law enforcement. The limitations of the results include a small sample size. Keywords: HRV, biofeedback, police officers, anxiety, stress, traumatic stress Í starfi sínu, upplifa lögregluþjónar streituvaldandi aðstæður, verða vitni að áfalla miklum atburðum, og þurfa að taka mikilvægar ákvarðanir undir miklu álagi. Þessar aðstæður geta haft áhrif á andlega heilsu lögregluþjónanna. Rannsóknir hafa sýnt að áhrif HRV biofeedback þjálfunar getur bætt andlega heilsu einstaklinga til muna. Þess vegna, miðar þessi rannsókn að því að kanna hvaða áhrif HRV biofeedback þjálfun hefur til að draga úr kvíða-, streitu- og áfallastreitueinkennum íslenskra lögregluþjóna. Rannsóknin fór fram yfir ...